Spatial metabolic heterogeneity of sugar–acid balance and pigment accumulation in distinct color regions of Yanzhihong apricot (Prunus armeniaca L.) revealed by MALDI-IMS - Zhao, Yang; He, Yanhong; Xing, Weiyuan; Bai, Yu-e; Li, Hui; Ye, Dongmei; Kang, Min (Frontiers in Plant Science, 2025)
This study is the first to apply spatial metabolomics techniques, MALDI-IMS to investigate differential distributions of sugars, organic acids, and pigments in the red and yellow regions of Yanzhihong apricot fruit. PCA and OPLS-DA analyses indicated that sucrose was significantly higher in the red region (21.39 mg/g) than in the yellow region (17.79 mg/g). In contrast, the yellow region exhibited significantly greater levels of fructose (31.54 mg/100g), ascorbic acid (11.03 mg/g), malic acid (3.61 mg/g), and citric acid (6.41 mg/g) than the red region (16.88mg/100g, 8.29, 2.34, and 4.27 mg/g, respectively). The red region also exhibited higher carotenoid levels (29.25 mg/g) and the anthocyanin cyanidin-3-O-(6’’-O-malonyl)glucoside, primarily in the peel and adjacent tissues, thereby enhancing pigment deposition and antioxidant capacity. These findings demonstrate notable spatial variability in sugar–acid metabolism and pigment accumulation between red and yellow fruit regions, which not only determine taste and color but also provide valuable insights for targeted fruit quality improvement and breeding of apricot cultivars with optimized sensory and nutritional traits.